Reintegration of Survivors of Human Trafficking: Dimensions and Prospects of Shelter Services - Rai, Mahendra Kumar (Tribhuvan University Journal, 2025)
The reintegration of survivors of human trafficking is challenging task. Shelter service offers services related to economic, social and psychological dimensions. This paper aims to assess the major dimensions of reintegration of shelter services and to explore the prospects of shelter services for successful and sustainable reintegration. A mixed-method research approach was applied to assess the dimensions and prospects of reintegration of shelter services for successful reintegration. The sample size for quantitative survey was 120 and for qualitative interview was 21. The respondents of the survey were survivors and concerned stakeholders whereas participants of KII and IDI were experts and survivors. This study is qualitative led so quantitative data was used to support and validate qualitative findings. Shelters are essential in preparing survivors for reintegration by offering comprehensive support that includes social, economic and psychosocial services. These services help survivors regain financial stability, emotional well being and social confidence, which are all vital for reintegration into family and community life. About two third survivors needed financial support whereas 14 percent aspired to take skill training which can be effectively facilitated by shelters. Of the total survivors, 53 percent male survivors had received training related to driving whereas 45 percent female survivors had received training related to tailoring. Shelters plays pivotal role to provide immediate, short-term and long-term services for making survivors empowered. The shelter care and support enhance survivors to become capable, aware and empower which leverage for successful reintegration. To enhance the impact of reintegration efforts, specific systems, strategies, and policies must be developed. The prospects of shelter services include creating a standalone reintegration policy for survivors, establishing a robust identification and data management system, improving the use and coordination of existing resources and strengthening inter-agency cooperation. These steps are pivotal for improving the long-term prospects of reintegration services.